Pelatihan Menjadi Master of Ceremony (MC) Acara Formal untuk Pelajar SMK - Yayu Sriwartini; Masnah Masnah; Neny Yusreini Sabrie; Ayu Lestari (Universitas Mathla'ul Anwar Banten, 2021)
TRAINING TO BECOME A MASTER OF CEREMONY (MC) FORMAL EVENTS FOR VOCATIONAL STUDENTS. Master of Ceremony training for formal events was given to students of SMKN 62 class XI Department of Office Administration and Public Relations. Situation and problem analysis were done by digging up information about the activities needed by students. The resulting agreement with the school was to hold a Master of Ceremony training for a formal event, which was done virtually through the zoom application. Apart from being still a pandemic, it was also because of the school's request. The activity was given in three stages, namely pre-test, material giving and post-test which included practice and evaluation. The aim of the training was to improve the communication skills of students in guiding formal events. The results of the training showed that there was a cognitive change, namely the addition of knowledge about the functions and standards of MC for formal events and the addition of knowledge of verbal and non-verbal language processing skills. In practice, the change seen was an increase in the quality of communication in presenting formal events. The participants' communication anxiety began to decrease and they began to have self-confidence. Overall, the MC training for formal events ran smoothly, but the skills of students to become MC still need to be improved continuously.